A MRI classification of periprosthetic soft tissue masses (pseudotumours) associated with metal-on-metal resurfacing hip arthroplasty. - Hauptfleisch, J; Pandit, H; Grammatopoulos, G; Gill, H; Murray, D; Ostlere, S (2012)
Metal-on-metal hip resurfacing arthroplasty (MoMHRA) has become a popular option for young patients requiring hip replacement. A recognised complication is the formation of a symptomatic reactive periprosthetic soft tissue mass (pseudotumour). We present a radiological classification system for these reactive masses, dividing them into three groups: Type I are thin-walled cystic masses (cyst wall <3 mm), Type II are thick-walled cystic masses (cyst wall >3 mm, but less than the diameter of the cystic component) and Type III are predominantly solid masses.